Application of the Talaqi Method in Taud At-Tartil Sukabumi - Siti Nur Afifah; Siti Qomariyah; Rima Erviana; Najrul J. Rizky; Neneng Nur (P3M IAI Nusantara Batang Hari, 2023)
Learning the tahfidz of the Koran is a process or activity of memorizing the verses of the Koran by repeating the readings either by listening to or seeing the writings of the Koran, so that the readings can stick in memory and can be repeated without having to look at the Koran and its writings. In memorizing the Koran, of course, there is a special method so that children can memorize it quickly and accurately. The results of research at TAUD At-Tartil used a unique method, one of which was the Talaqi method. Based on the observations that the researchers made, children memorize using this method because one of the factors is choosing the right method that will make it easier for children to memorize. Therefore, this study aims to find out how the implementation of the Talaqi Method in Learning Al-Qur'an Tahfidz at TAUD At-Tarti Sukabumi. The type of research used is descriptive qualitative research. Methods of data collection using interviews, observation, and documentation. With this method it can anticipate students memorizing the Koran so that it is easier to memorize the Koran because it is always heard and repeated by students, and this method is flexible and can be done anywhere without having to always use it in class.